2017
DOI: 10.1155/2017/9679843
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between HLA-DQ Gene Polymorphism and Hepatitis B Virus Infection

Abstract: Hepatitis B virus (HBV) infection is the predominant risk factor for chronic hepatitis B (CHB). The association between HBV infection and human leukocyte antigen- (HLA-) DQ polymorphism (rs2856718 and rs7453920) has been demonstrated in other studies; however, the results were controversial or inconclusive. Therefore, to derive a more precise estimation of the association, a meta-analysis was performed. Crude odds ratios (ORs) and their 95% confidence intervals (CIs) were used to assess the strength of associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
(40 reference statements)
0
11
0
1
Order By: Relevance
“…Vermehren et al (Vermehren et al, 2012) failed to confirm an association of HLA-DPB1 rs9277535 with hepatitis B in Caucasians. A comprehensive meta-analysis suggested that HLA-DP/DQ (rs3077, rs9277535, rs9275572, rs9275319, rs2856718, and rs7453920) is associated with susceptibility to HBV or the clearance of HBV infection (Zhang et al, 2013e; Yu et al, 2015; Xu et al, 2017b; Xu et al, 2018). A meta-analysis by Huang et al (Huang et al, 2016) suggested that HLA-DQB1*0201, DQB1*0301, and DQB1*0502 are associated with an increased risk of CHB (chronic hepatitis B), while HLA-DQB1*0303 and DQB1*0604 are associated with a decreased risk of CHB.…”
Section: Chronic Hbv Infectionmentioning
confidence: 99%
“…Vermehren et al (Vermehren et al, 2012) failed to confirm an association of HLA-DPB1 rs9277535 with hepatitis B in Caucasians. A comprehensive meta-analysis suggested that HLA-DP/DQ (rs3077, rs9277535, rs9275572, rs9275319, rs2856718, and rs7453920) is associated with susceptibility to HBV or the clearance of HBV infection (Zhang et al, 2013e; Yu et al, 2015; Xu et al, 2017b; Xu et al, 2018). A meta-analysis by Huang et al (Huang et al, 2016) suggested that HLA-DQB1*0201, DQB1*0301, and DQB1*0502 are associated with an increased risk of CHB (chronic hepatitis B), while HLA-DQB1*0303 and DQB1*0604 are associated with a decreased risk of CHB.…”
Section: Chronic Hbv Infectionmentioning
confidence: 99%
“…Chang et al, who studied the effect of HLA variants and response to interferon therapy in male Han Taiwanese patients with CHB, concluded that "G-C" haplotype of the five SNPs, including rs9277535 (HLADPB1), rs9276370 (HLA-DQA2), rs7756516 and rs7453920 (HLA-DQB2), and rs9366816 near HLA-DPA3, is associated with sustained therapeutic response to IFN-α treatment [22]. In addition, results of a meta-analysis performed by Xu et al concluded that the HLA-DQ rs7453920-A allele was a protecting factor against chronic HBV infection, while rs 7453920-G serves as a risk factor for HBV infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a single study, meta-analysis can provide sufficient results especially in analyzing unexplained studies [ 56 ]. In our previous meta-analysis including 11 case-control studies, we demonstrated that HLA-DQ rs2856718-G polymorphism showed protective effects against HBV infection, and rs2856718-A was a risk factor for chronic HBV infection [ 57 ]. Subsequently, Meta-analysis by Lv et al showed that rs2856718 and rs9275572 in HLA-DQ significantly decreased HBV-related HCC in total population, especially in Chinese other than in Saudi Arabian [ 58 ].…”
Section: Discussionmentioning
confidence: 99%